Spatial coverage of Forest habitat types under Natura 2000 in Zadar County (Journal of Forestry, 2025)
In three biogeographic regions in Zadar County, there are three forest target habitat types, one of which is identified as a priority habitat type. Spatial analyses are essential for effective planning and management of Natura 2000 sites, which is why they were chosen as the aim of this research. Geoprocessing methods in ArcGIS were used to create new values, with the goal of calculating the areas of forest target habitat types in the Natura 2000 sites in Zadar County. By using GIS (Geographic Information System) tools, the result obtained was that forest habitat types in Zadar County cover 6,849.56 ha, accounting for 5.55% of the land area of the Natura 2000 sites important for species and habitat types, or 1.88% of the land area of the county. The general condition of the forest target habitat types in Zadar County ranges from good, very good to excellent. However, there is a high risk of forest fires, and climate change poses a significant threat. It is necessary to establish a monitoring system of the forest target habitat types' condition. The results of this research may be used as a basis for further studies and planning of the conservation of natural habitats within the Natura 2000 sites in Zadar County.